RESEARCH THE MATURITY OF PROJECT ACTIVITY OF POWR SUPPLY COMPANIES - Savka, Y. V. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The urgency of the project activity for providing of the development of the power supply enterprises is substantiated. It is generalized that the project activity allows the flexibly approach to the question of finance sources finding for measures aimed to the development of enterprises. The preconditions and trends of implementation of the project activity in the domestic practice are substantiated. The method of evaluation of the level of maturity of the project activity of power supply companies that is based on the selection and characteristics of the stages of this process is proposed, the key criteria of implementation and improvement of the project activity at the power supply enterprises are determined. The current level of maturity of the project activity is identified on the example of the electricity supply company. Strengths, weaknesses, as well as opportunities and threats of implementation of the project activity for the investigated enterprises are highlighted. Measures to implement the project activity at power supply companies are proposed.